(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2016)
Background: Total splenectomy, exposes children to the high risk of overwhelming postsplenectomy infections (OPSI). To avoid these adverse consequences, partial splenectomy has long been practiced for thalasseemia in children. It has been reported that the partial splenectomy keeps the child immunologically competent, hematologically stable with minimum blood transfusion and makes their life more comfortable in comparison to total splenectomy. Objectives: To compare the results of partial and total splenectomy. Methodology: This prospective interventional comperative study was done in the department of Pediatric Surgery, BSMMU from 2010 to 2012. Children who underwent partial splenectomy were considered as the case and who underwent total splenectomy as the control. Number of blood (RCC) transfusions (ml/ kg/year), Peripheral blood film (Hb%, WBC count, platelet count, Howell-Jolly body, serum bilirubin), volume of liver (ml), volume of spleen (ml), number of OPSI case, were compared between the case and control groups both pre and postoperatively. Results: Postsplenectomy blood transfusion requirement is comparatively more decreased in control group than case group. The inter group difference at 6 month is significant (p= 0.004). Peripheral blood pictures are improved in both groups. Post splenectomy hemoglobin level was increased in both groups but it was maintained at a more static fashion in control group than case group (P = 0.114). Howell-jolly body in the partial splenectomy group disappeared almost completely at month 6, while the same inclusion body in the total splenectomy group appeared in all the children (p= 0.001). There was no postsplenectomy infection in case group while two found in control group. After partial splenectomy the residual volume of the spleen was gradually increasing. The increase in volume of the liver was notably greater in the total splenectomy group than that in the partial splenectomy group (p< 0.05). Conclusion: Partial splenectomy in patients with ²-thalassemia is effective in controlling hemolysis, improving peripheral blood picture while preserving the residual splenic phagocytic and immune function. J. Paediatr. Surg. Bangladesh 6(2): 39-46, 2015 (July)